A Guinada para o Atlântico Sul: a influência do Brasil nas relações ao leste e a diversificação de parcerias com a África Ocidental - Bravo e Paiva, Ana Luiza; Monfredo Mendes, Cintiene Sandes; Medeiros, Sabrina Evangelista (Hemisferio - Revista del Colegio Interamericano de Defensa, 2019)
The focus of this paper is to evaluate Brazil's shift toward the South Atlantic. The central argument of the text addresses the increasing importance of relations with Africa as part of the Brazilian political agenda attributed to the disputes and obstacles identified in various South America integration proposals. In this scenario, Brasilia has opted to adopt a strategy aimed at diversifying its partnerships with a greater focus on West Africa. In that regard, the paper provides, throughout its contents, evidence of Brazilian technical cooperation that help to reinforce the concept of triangulation and the diversification of partners.